A língua inglesa como objeto e instrumento mediador de ensino-aprendizagem em educação bilíngüe - Cortez, Ana Paula Barbosa Risério (2007)
The aim of this work is to discuss the role of the English language as a mediating tool in bilingual education. The study is grounded on the social-historical-cultural Activity Theory (Vygotsky, 1933-1935/1934, Leontiev, 1977-1978), which is founded by the dialogical comprehension of language (Bakhtin, 1981). Besides, it also presents some of the conceptions of bilingual education based on the work of Hamers and Blanc (2000). This is a critical action-research (Kincheloe, 1997), since there is evaluation, reflection and reconstruction of practice, in a critical paradigm, inserted in the context of bilingual education. It aims at the transformation and new alternatives for the ones involved in the research and at new horizons in the bilingual teaching-learning process. This research includes the researcher-teacher and the group of grade six students at a bilingual school in the city of São Paulo. The study was carried out in the second term in 2005 and the material collected is composed of selected video recordings of the classes taught in that term. The results point out to the English language being the teaching-learning object in English classes, in an enunciative point of view, being built up to become a tool-for-result when it is used without questionings that expand the understanding of the students about the language itself. It is a tool-and-result when it is interpreted, contested and expanded throughout debates between the teacher and the students. English is the object in social studies classes when it refers to new vocabulary, grammatical content or genres that may be part of the activity. It is a tool-for-result when used without a broad reflection or a major examination made by the students concerning concepts of the area. The English language is a tool-and-result in social studies classes in situations in which there are questions that expand and correlate concepts, and the subjects of the activity deal with the language beyond its structure. It also is used to constitute the object of social studies classes. Therefore, the results of this analysis indicate that, in this perspective, language expands itself and the area content, in both subjects